Photochemical C3-amination of pyridines via Zincke imine intermediates - Kitti Franciska Szabó; Piotr Banachowicz; Antoni Powała; Danijela Lunic; Ignacio Funes Ardoiz; Dorota Gryko (Nature Communications)
Abstract Selective skeletal and peripheral editing of the pyridine moiety has broadly expanded the chemical space. While C-H functionalization at C2 and C4 positions are enabled by the inherent reactivity of this heteroarene, selective derivatization at the C3 position has long posed a significant challenge. Recently, based on a dearomatization-rearomatization sequence, involving Zincke imine intermediates, selective halogenation (-Br, -Cl, and -I) and isotopic labelling were accomplished. Here, we report a mild and regioselective method for C3-amination that relies on the photochemical reaction of Zincke imine with an amidyl radical generated from N-aminopyridinium salts. Mechanistic and theoretical studies indicate that radical intermediates are involved and explain the C3 regioselectivity of the reaction.